2016
DOI: 10.1186/s13054-016-1579-8
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol levels and long-term rates of community-acquired sepsis

Abstract: BackgroundDyslipidemia is a risk factor for cardiovascular disease, with elevated low-density lipoprotein cholesterol (LDL-C) and decreased high-density lipoprotein cholesterol (HDL-C) recognized as risk factors for acute coronary events. Studies suggest an association between low cholesterol levels and poor outcomes in acute sepsis. We sought to determine the relationship between baseline cholesterol levels and long-term rates of sepsis.MethodsWe used data from the Reasons for Geographic and Racial Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 54 publications
(45 reference statements)
3
61
2
1
Order By: Relevance
“…Rapid drops in both HDL and LDL cholesterol have been reported in previous studies, 57 and our group recently demonstrated that low LDL is a risk factor for long-term community-acquired sepsis. 8 Similarly, in this study, patients with adverse outcomes experienced more severe drops in LDL. There may be several reasons for early drops in lipid concentrations during sepsis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Rapid drops in both HDL and LDL cholesterol have been reported in previous studies, 57 and our group recently demonstrated that low LDL is a risk factor for long-term community-acquired sepsis. 8 Similarly, in this study, patients with adverse outcomes experienced more severe drops in LDL. There may be several reasons for early drops in lipid concentrations during sepsis.…”
Section: Discussionsupporting
confidence: 57%
“…7 Most recently, our group demonstrated that low LDL-C levels were predictive of long-term community acquired sepsis risk. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Low LDL-C levels were associated with increased risk of death in patients with community-acquired pneumonia 9 and with increased risk of sepsis in hospitalized patients 7 ; also, sepsis outcomes were worse than those of patients with high LDL-C levels. 8 , 10 However, these studies do not necessarily implicate LDL-C directly as a modifier of sepsis because the confounding effects of comorbid illness could account for the findings (ie, sicker patients could have lower LDL-C levels and worse outcomes). An epidemiologic study of approximately 30 000 community-dwelling adults was less prone to confounding and showed that lower LDL-C levels at entry to the cohort were associated with increased risk of future sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low levels of LDL cholesterol (LDL-C) have an increased risk of sepsis and worse outcomes 7 , 8 , 9 ; however, these studies do not answer the question whether LDL-C modifies the risk of sepsis and poor outcomes directly, or if it does so indirectly through the effects of comorbid illness. A study performed in community-dwelling adults 10 showed that low LDL-C levels at entry to the cohort were associated with an increased risk of future sepsis, suggesting that LDL-C levels could affect the risk of sepsis directly.…”
Section: Introductionmentioning
confidence: 99%
“…They are not only considered as the components of membranes and source, but also act as an indispensable factor in the immune response by organizing signalling complexes in cellular membrane [9]. Studies have confirmed that lipids act as important inflammatory mediators during infection process [7,[9][10].…”
Section: Introductionmentioning
confidence: 99%